Day 3 Wed, February 23, 2022 2022
DOI: 10.2523/iptc-22399-ea
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Recovery and Re-Use of Commercial Kinetic Hydrate Inhibitors from Produced Water and Rich Glycol

Abstract: Kinetic hydrate inhibitors (KHIs) offer an alternative to traditional thermodynamic hydrate inhibitors (THIs) for the prevention of gas hydrates. KHIs have several advantages over THIs, such as lower required volumes, easier logistics and reduced CAPEX. However, KHIs are once through chemicals leading to increased OPEX, are mostly non-biodegradable and therefore cannot be discharged to sea or disposal wells in fear of aquifer pollution. KHIs can also lead to fouling of process equipment, especially at elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Furthermore, industry regulators have concluded that the presence of KHI polymers in the injected wastewater leads to long-term reservoir damage (Golpour and Pakizeh, 2017;Li et al, 2019;Wang et al, 2019;Saberi et al, 2021). The removal of KHIs by physicochemical techniques (nanofiltration, adsorption) was the subject of few studies (Anderson et al, 2016;Golpour and Pakizeh, 2017;Dehghan et al, 2021;Mozaffar et al, 2022). These techniques failed to remove high amounts of KHIs from wastewater further to their expensive costs, strict operational conditions, and production of secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, industry regulators have concluded that the presence of KHI polymers in the injected wastewater leads to long-term reservoir damage (Golpour and Pakizeh, 2017;Li et al, 2019;Wang et al, 2019;Saberi et al, 2021). The removal of KHIs by physicochemical techniques (nanofiltration, adsorption) was the subject of few studies (Anderson et al, 2016;Golpour and Pakizeh, 2017;Dehghan et al, 2021;Mozaffar et al, 2022). These techniques failed to remove high amounts of KHIs from wastewater further to their expensive costs, strict operational conditions, and production of secondary pollution.…”
Section: Introductionmentioning
confidence: 99%